Impact of interoperability regulation on the use of digital payments in Peru - Celene Ancalle; Maria Gracia Garcia (Graduate Institute of International and Development Studies, 2024)
Interoperability is the characteristic of a payment service (e.g. digital wallets) to allow its users to pay any person or company, regardless of the financial institution providing services to the payer or payee. On October 7, 2022, the Central Reserve Bank of Peru (BCRP) issued the Payment Services Interoperability Regulation to massify digital payments in the country. The main objective of this research is to study the impact of interoperability, promoted through regulation, on the use of digital payments. We analyzed transactional data provided daily by market participants in the interoperability regulation, and data obtained from digital wallet users through a survey. The results suggest that interoperability has contributed to increase the use of digital payments, but there are other factors such as fees, user experience and quality of service that can impact the adoption and use of interoperable payment services. Furthermore, our analysis shows that interoperability benefited more individuals in regions with a higher degree of financial inclusion, i.e. financial inclusion is key to benefiting from interoperability. These results serve as a basis for validating, adjusting, and reorienting the future regulatory strategies of the BCRP, aimed at fostering greater adoption and use of digital payments; as well as to guide other payment authorities seeking to implement effective digital payments regulations, drawing lessons from the Peruvian experience.
Keywords: E42; E58; E61; E65; G28; 330; Interoperability; regulation; digital payments; financial inclusion; Peru